Rebus Approach of Entrepreneurship Learning - Jelena Jovanovic; Zdravko Krivokapic; Aleksandar Vujovic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
In the Western Balkan countries young generations prefer “safe” employment at public enterprises. Student's awareness and appreciation of own entrepreneurship potentials are low and because of that they mostly don't start their own business. It is obvious that there is a need to promote learning about entrepreneurship at the HEIs and need to strengthen capacities of university lecturers to deal with entrepreneurship topics. The Erasmus REBUS project is established with aims to promote entrepreneurship competences of graduates of engineering studies from the Western Balkan countries and Russia, through development, test, validation and mainstreaming of holistic and needs driven open learning modules. The project enabled strong support to address a challenge of bringing entrepreneurship into HEIs and establishing the interface between higher education and practical business context based on cooperation network of EU and Western Balkan countries. The paper is focused on Rebus approach of entrepreneurship learning in Western Balkan countries. REBUS project promote development of various entrepreneurship training modules and their integration into existing or new curricula at the HEIs, creation and adoption of entrepreneurship competence validation system, implementation and evaluation of the training modules and competence validation system. There will be also shown how Rebus project is implemented at the University of Montenegro, with focus at the process of learning about entrepreneurship, process of definition and realization of students' project and validation of their knowledge.
Keywords: L26; 330; Entrepreneurship; competences; blended learning; validation